From the WHO framework to integrated senior health and wellness hub program: an implementation journey - Huang, Xiaoting; Tan, Hao Yi; Er, Pei Ling; Wong, Amber; Lim, Si Qi; Kuan Tan, Joshua; Yee, Wan Qi; Xin, Xiaohui; Low, Lian Leng (Frontiers in Public Health, 2025)
IntroductionAs global populations age, ensuring older adults maintain functional ability and wellbeing is a critical public health priority. The Integrated Senior Health and Wellness (ISHW) Hub program, developed by Singapore General Hospital (SGH), operationalizes the World Health Organization’s (WHO) Integrated Care for Older People (ICOPE) framework within community-based models of care. Implemented in partnership with Active Aging Centers (AACs), ISHW enhances preventive health through structured screening, customizable nutrition education, and targeted physical activity interventions.MethodsThis study aimed to develop an implementation-informed, context-sensitive model for integrated care using the Consolidated Framework for Implementation Research (CFIR) and Theory of Change to guide the design and pilot of the ISHW program. The ISHW program employs a multi-prong approach, integrating health interventions with social engagement to address both physical and psychosocial determinants of health. Key components include community-driven intrinsic capacity assessment including chronic disease screening for early detection, dietitian-curated nutrition education and exercise program enhanced by physiotherapist. A critical innovation is the “train-the-trainer” model, which enhances capacity-building among AAC staff and volunteers which supports sustainable program delivery.ResultsQualitative insights were gathered from 5 focus groups (n = 20) and 1 feedback group (n = 10), analyzed thematically through consensus-driven coding. Early implementation findings highlight the feasibility of integrating ICOPE principles within community-based settings, but also underscore key challenges, including resource constraints and the need for stronger inter-sectoral coordination. Facilitators of success include structured capability-building, community participation, and alignment with national aging policies such as Age Well SG and Healthier SG. Findings gleaned from CFIR and ToC was operationalized to a program’s logic model that was iteratively refined to enhance adaptability and scalability across diverse community settings.DiscussionThis case study adds to current understanding of community-centered models for promoting healthy aging and helps to serve as a guidance on how ICOPE-based program could be adapted to other community settings for integrating health and social care to support aging in place. Future evaluations will assess longitudinal outcomes and inform the scalability of community-based ICOPE implementation strategies.